2019
DOI: 10.1039/c9ee00269c
|View full text |Cite
|
Sign up to set email alerts
|

Phase-transition induced giant negative electrocaloric effect in a lead-free relaxor ferroelectric thin film

Abstract: Ferroelectric/antiferroelectric thin/thick films with large positive or negative electrocaloric (EC) effects could be very useful in designing commercial refrigeration devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 57 publications
2
48
1
1
Order By: Relevance
“…Due to the applied electric field, a uniform rhombohedral phase transition occurs along the out-of-plane direction ( Figure 27 a). We proved this speculation by building a phase change model [ 92 ] ( Figure 27 b).…”
Section: Electrocaloric ( Ec ) Refrigerationmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to the applied electric field, a uniform rhombohedral phase transition occurs along the out-of-plane direction ( Figure 27 a). We proved this speculation by building a phase change model [ 92 ] ( Figure 27 b).…”
Section: Electrocaloric ( Ec ) Refrigerationmentioning
confidence: 86%
“…Lead-free relaxor ferroelectric thin film 0.5(Ba 0.8 Ca 0.2 )TiO 3 -0.5Bi(Mg 0.5 Ti 0.5 )O 3 (BCT-BMT) was prepared on Pt(111)/TiO x /SiO 2 /Si substrate by sol-gel method [ 92 ]. The BCT-BMT films have large energy density of 51.7 J·cm −3 and a high power density of 1.15 × 10 10 W·kg −1 at room temperature ( Figure 21 ).…”
Section: Thin-film Energy Storage Performancementioning
confidence: 99%
“…The characteristics of the material are slow change of dielectric constant and enhanced ECE peaks (up to 12 K) at the T c , which is in accord with α 0 = 0.5. Peng et al reported giant ECE in relaxor Pb 0.8 Ba 0.2 ZrO 3 thin films, large‐positive or ‐negative ECE in Ferroelectric/antiferroelectric thin/thick films . The giant ECE peak of 45.3 K in Pb 0.8 Ba 0.2 ZrO 3 thin films at 290 K away from its Curie temperature (408 K) can be attributed to the ferroelectric coupling effect, which has more significant influence than the two others showing small twin‐peak ECEs at about 408 K. The negative ECE in antiferroelectrics should be originated from antiferroelectric coupling between neighbor dipoles in opposite directions which is the unique difference between antiferroelectric and ferroelectric materials.…”
Section: Discussionmentioning
confidence: 99%
“…As Liu and Ren proposed a critical triple point MPB composition, exploring the morphotropic phase boundary (MPB) system could be an effective method to seek high-performance BCZT materials with excellent dielectric properties to be utilized for energy storage purposes. We also upgraded BCT-BZT to BCT-BMT and achieved excellent dielectric and energy storage properties which appeal the scientific community to try such up gradations [133,134]. Furthermore, these ceramics are sintered at too high temperatures, meaning that their synthesis process is hardly reproducible and the composition homogeneity is rather uncontrollable.…”
Section: Bczt Thin Films For Enhancement Of Dielectric Propertiesmentioning
confidence: 99%